COGNITIVE CONCEPTUALISATIONS OF POLITICAL EUPHEMISTIC EXPRESSIONS - Suparto Suparto; Ayyuhatsanail Fithri (Journal of Language and Literature, 2022)
This paper discusses political euphemistic expressions from the perspective of cognitive linguistics. It is human to say something naturally and socially acceptable, emotionally not irritating, logically intelligible, and communicatively inter-translatable. Euphemistic expression is a way with which language speakers’ experiences can be linguistically and cognitively manifested. As a soft word or expression which is used to denote to things about which people may find disappointing or embarrassing to talk, euphemistic expressions enable to say something impossible possible. Introspection as a deep understanding of any language speaker to his/her language system on any talks is used as the data analyzing method. Research data is taken from online mass media. The research data focuses on politically related euphemistic expressions. The accounts of Conceptual Metaphor Theory (CMT) are used to give insights into the cognitive mechanism of euphemistic expressions. Political euphemistic expressions are logically intelligible. The research findings demonstrate that there are two basic motivations of euphemizing political expressions. The two are function and characteristics. The internalization of language speaker to the primordial nature of something to euphemize is the key to understand the way to construct the euphemistic expressions.